Finite Solutions Of Fully Fuzzy Linear System - Malkawi, Ghassan; Ahmad, Nazihah; Ibrahim, Haslinda (2014)
The solution of Fully Fuzzy Linear System (FFLS) is normally categorized as unique, finite and infinitely many solutions. However, in the case of more than one solution, the finite or alternative solution is not detected when linear programming is considered. Therefore this paper aims to provide a method of using min-max system and absolute system to append new concept for the consistency of FFLS, which is called finite solution of FFLS, where the FFLS have more than two solutions, and not only an infinite solution